The Potential Effect of Lidocaine, Ropivacaine, Levobupivacaine and Morphine on Breast Cancer Pre-Clinical Models: A Systematic Review - Matos, Ana Catarina (2022)
Breast cancer (BC) is one of the most common types of cancer and the second leading cause of death in women. Local anaesthetics (LAs) and opioids have been shown to influence cancer progression and metastasis formation in several pre-clinical studies. However, their effects do not seem to promote consensus. A systematic review was conducted using the databases Medline (via PubMed), Scopus, and Web of Science (2010 to December 2021). Search terms included "lidocaine", "ropivacaine", "levobupivacaine", "morphine", "methadone", "breast cancer", "breast carcinoma" and "breast neoplasms" in diverse combinations. The search yielded a total of 784 abstracts for initial review, 23 of which met the inclusion criteria. Here we summarise recent studies on the effect of analgesics and LAs on BC cell lines and animal models and in combination with other treatment regimens. The results suggest that local anaesthetics have anti-tumorigenic properties, hence their clinical application holds therapeutic potential. Regarding morphine, the findings are conflicting, but this opioid appears to be a tumour-promoting agent. Methadone-related results are scarce. Additional research is clearly required to further study the mechanisms underlying the controversial effects of each analgesic or LA to establish the implications upon the outcome and prognosis of BC patients' treatment.